Happily Distracted: Mood and a Benefit of Attention Dysregulation in Older Adults - Biss, Renée K.; Weeks, Jennifer C.; Hasher, Lynn (Frontiers in Psychology, 2012)
Positive mood states are believed to broaden the focus of attention in younger adults, but it is unclear whether the same is true for older adults. Here we examined one consequence of broader attention that has been shown in young adults: that memory for distraction is greater for those in a positive mood. In the current study, positive and neutral moods were induced in older adults (M = 67.9) prior to a 1-back task in which participants were instructed to attend to relevant pictures and ignore distracting words. Following a 10-min filled interval, participants performed a word fragment completion task that tested implicit memory for the distracting words from the 1-back task. Older adults in the positive mood group showed greater implicit memory for previous distraction compared to those in the neutral mood group. These findings suggest that affect influences the ability to regulate attention in a similar manner for younger and older adults.